2016
DOI: 10.1159/000444357
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating Lymphocytes: A Promising Biomarker in Breast Cancer

Abstract: There is clear evidence that the immune system plays an essential role in tumor defense. By determining tumor-infiltrating lymphocytes (TILs), the individual immunological response becomes more apparent and measurable. In breast cancer, high levels of TILs are associated with a more favorable clinical course. In this review, we describe how TILs are determined with emphasis on daily routine diagnostics. We further discuss their impact as a prognostic and predictive biomarker in the neoadjuvant and adjuvant the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…They are a population of cells comprising a mixture of cytotoxic T cells and helper T cells, as well as B cells, macrophages, natural killer cells, and dendritic cells. Whilst not discussed extensively in this manuscript, gene expression and flow cytometry profiles demonstrate that TIL quantity, as assessed semiquantitatively on a hematoxylin and eosin (H&E) stained slide, represents a surrogate for a pre-existing favourable host anti-tumor activated T cell response ( 4 , 5 ).…”
Section: Background: the Immune System And Tils In Breast Cancermentioning
confidence: 99%
“…They are a population of cells comprising a mixture of cytotoxic T cells and helper T cells, as well as B cells, macrophages, natural killer cells, and dendritic cells. Whilst not discussed extensively in this manuscript, gene expression and flow cytometry profiles demonstrate that TIL quantity, as assessed semiquantitatively on a hematoxylin and eosin (H&E) stained slide, represents a surrogate for a pre-existing favourable host anti-tumor activated T cell response ( 4 , 5 ).…”
Section: Background: the Immune System And Tils In Breast Cancermentioning
confidence: 99%
“…TILs are widely considered to be a key indicator of the immune interaction between host and tumor, and potentially effective predictive biomarkers of cancer immunogenicity, clinical outcome, response to immunotherapy and other antitumor treatments [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Although lymphocytic infiltrates have long been observed in breast cancer, only recent clinical trials have demonstrated the immunogenic nature of breast cancer and the potential role of host immunosurveillance in influencing tumor progression and treatment responses [ 5 , 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. B-cell infiltrates seem to play only a minor role in mammary tumor, where CD20+ cells are sporadically detected [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] This applies to the composition of the immune infiltrate at diagnosis, [1][2][3][4]8,9 as well as for the dynamic changes induced by anthracycline-based chemotherapy, in which an amelioration of the ratio of CD8…”
Section: Introductionmentioning
confidence: 99%